Photo-electron momentum distribution and electron localization studies from laser-induced atomic and molecular dissociations - Ray, Dipanwita (Kansas State University, 2010)
The broad objective of ultrafast strong-field studies is to be able to measure and control atomic and molecular dynamics on a femtosecond timescale. This thesis work has two major themes: (1) Study of high-energy photoelectron distributions from atomic targets. (2) Electron localization control in atomic and molecular reactions using shaped laser pulses. The first section focuses on the study of photoelectron diffraction patterns of simple atomic targets to understand the target structure. We measure the full vector momentum spectra of high energy photoelectrons from atomic targets (Xe, Ar and Kr) generated by intense laser pulses. The target dependence of the angular distribution of the highest energy photoelectrons as predicted by Quantitative Rescattering Theory (QRS) is explored. More recent developments show target structure information can be retrieved from photoelectrons over a range of energies, from 4U$_p$ up to 10U$_p$, independent of the peak intensity at which the photoelectron spectra have been measured. Controlling the fragmentation pathways by manipulating the pulse shape is another major theme of ultrafast science today. In the second section we study the asymmetry of electron (and ion) emission from atoms (and molecules) by interaction with asymmetric pulses formed by the superposition of two colors (800 $\&$ 400 nm). Xe electron momentum spectra obtained as a function of the two-color phase exhibit a pronounced asymmetry. Using QRS theory we can analyze this asymmetric yield of the high energy photoelectrons to determine accurately the laser peak intensity and the absolute phase of the two-color electric field. This can be used as a standard pulse calibration method for all two-color studies. Experiments showing strong left-right asymmetry in D$^+$ ion yield from D$_2$ molecules using two-color pulses is also investigated. The asymmetry effect is found to be very ion-energy dependent.
Keywords: AMO; Physics, Atomic (0748)